Decision analysis of students’ smoking behavior in Yogyakarta: Attitudes, knowledge, and health-economic safety - Armansyah, Ferry; Dewanti, Diah Setyawati (Jurnal Ekonomi & Studi Pembangunan, 2025)
Smoking remains a major global health concern and continues to be prevalent among university students. This study aims to analyze the determinants of smoking behavior among students from four Islamic universities in Yogyakarta by examining the influence of attitudes, knowledge, community well-being, and health-related economic safety on smoking decisions. A cross-sectional quantitative survey was conducted involving 426 respondents selected through accidental sampling. Data were collected using a Likert-scale questionnaire and analyzed using binary logistic regression with SPSS software. The results revealed that 38.5% of respondents were smokers, with notable differences across campuses. Attitudes toward smoking had the strongest effect on smoking decisions (p = 0.000), indicating that negative attitudes significantly reduce the likelihood of smoking. Knowledge of smoking risks was not statistically significant (p = 0.553), while community well-being and economic safety showed varying influences on smoking behavior. This study extends the literature on health economics and behavioral decision-making by integrating psychosocial and economic safety dimensions into the analysis of student smoking behavior in Islamic university contexts. The findings suggest that anti-smoking interventions emphasizing attitude formation may be more effective than those solely focused on knowledge dissemination. University administrators and policymakers should develop culturally sensitive, campus-specific health education programs to reduce smoking prevalence. The cross-sectional design limits causal inference, and the sample may not fully represent all Indonesian universities. Future research could adopt longitudinal designs or incorporate qualitative approaches to better understand behavioral change mechanisms.